A three dimensional foot fourier descriptors model - Rijal, Omar Mohd; Hamzah, Mohd Faizal Mohd; Sankaraiah, S.; Noor, Norliza Mohd (Asian Research Publishing Network, 2018)
Knowledge of the 3D foot shape is important for the shoe industry, in particular, to provide comfort and fit to the users. In this study a random sample of 150 Malaysian adult women aged 19-60 years feet were scanned using the Infoot scanner system. Fourier Descriptor (FD) was then used to reconstruct a new model, with additional properties, and labeled as the FD foot model from the 3D homologous model. Six similarity measures and the Bland-Altman plot showed that the 3D FD foot model is almost identical to the 3D homologous model. Measurements of foot length, foot width and ball girth from both types of models were found to be almost identical. The FD terms was then showed to have a complex normal probability distribution which allows a way of quantifying the variability of individual points. This knowledge will be of great use for the shoe industry.